Construction and characterization of a multiwire proportional chamber detector - Castro Serrato, Hector Fabio; Delgado Gonzalez, Maritza Juliette (Universidad Pedagógica y Tecnológica de Colombia, 2019)
We have built and characterized a gaseous particle detector of the type “multiwire proportional chamber”, known as MWPC. The detector consists of an electronic circuit inside a hermetically sealed acrylic box, in an appropriate atmosphere of gas. Once the mechanical and electrical operation was verified, we performed the characterization as a particle detector. We measured the characteristic curve, consisting of the electrical charge collected at the electrodes, as function of applied voltage. Then we measured the count rate, for muons from cosmic radiation, versus voltage, known as “Plateau curve”. These measurements were performed with different mixtures of gases: 100%Air, 100% Ar, 100% CH4 and 90% Ar+10% CH4 (P10). In the results we discuss the operation of the detector at different voltages, for these gas mixtures. The best performance was obtained with the P10 mixture, for which, the detector works in the proportional region, for voltages between 3700 V to 4000 V, with an optimal operating voltage of 3850 V.